Mosaic evolution in an asymmetrically feathered troodontid dinosaur with transitional features - Xu, Xing; Currie, Philip; Pittman, Michael; Xing, Lida; Meng, Qingjin; Lü, Junchang; Hu, Dongyu; Yu, Congyu (Nature communications, 2017)
Asymmetrical feathers have been associated with flight capability but are also found in species that do not fly, and their appearance was a major event in feather evolution. Among non-avialan theropods, they are only known in microraptorine dromaeosaurids. Here we report a new troodontid, Jianianhualong tengi gen. et sp. nov., from the Lower Cretaceous Jehol Group of China, that has anatomical features that are transitional between long-armed basal troodontids and derived short-armed ones, shedding new light on troodontid character evolution. It indicates that troodontid feathering is similar to Archaeopteryx in having large arm and leg feathers as well as frond-like tail feathering, confirming that these feathering characteristics were widely present among basal paravians. Most significantly, the taxon has the earliest known asymmetrical troodontid feathers, suggesting that feather asymmetry was ancestral to Paraves. This taxon also displays a mosaic distribution of characters like Sinusonasus , another troodontid with transitional anatomical features. Troodontids were theropod dinosaurs closely related to birds. Here, Xu and colleagues describe a new, feathered troodontid species, Jianianhualong tengi , dating from the Lower Cretaceous period in China that provides insight into troodontid mosaic evolution and paravian feathering.